KEUTAMAAN BELAJAR DAN MENGAJARKAN AL-QURAN: Metode Maudhuâi dalam Perspektif Hadis - Muzakkir, Muzakkir (Lentera Pendidikan, 2015)
Abstract: Expression of the Prophet in the his words Ø®ÙÙÙØ±ÙÙÙÙÙ ÙÙÙÙ ØªÙØ¹ÙÙÙÙÙÙ Ø§ÙÙÙÙØ±ÙØ¢ÙÙ ÙÙØ¹ÙÙÙÙÙÙÙÙ need to be examined/investigated its validity in order to generate high motivation for Muslims to practice it. Based on the search results of sanad and Matan of the hadith through many sources and where the focus of the study were Jami at-Tirmidhi, it can be concluded that the quality of hadithÂ  was valid. Thus, the Quran as a perfect reading for Muslims who has certain rules in reading, from the mention of the letters, the short or the length, the thickness and the provisions of makharijul of letters need to be learned and taught diligently and earnestly. Learning al-Quran includes efforts to learn how to read them, to translate and to understand the laws, the lessons, the instructions contained therein. Likewise, teaching al-Quran includes efforts to lead and guide people to read, to translate and to understand the content of the verses of al-Quran. People who do it sincerely and earnestly will get the primacy of the al-Quran in the form of tranquility, peace of heart and mind as well as the intercession in the hereafter.Abstrak: Ungkapan Rasulullah saw. dalam sabda beliau Ø®ÙÙÙØ±ÙÙÙÙÙ ÙÙÙÙ ØªÙØ¹ÙÙÙÙÙÙ Ø§ÙÙÙÙØ±ÙØ¢ÙÙ ÙÙØ¹ÙÙÙÙÙÙÙÙ perlu diÂkaÂjiÂ/diÂteliti kesahihannya agar dapat menimbulkan motiviasi yang tinggi bagi umat IsÂlam untuk mengamalkannya. Berdasarkan hasil penelusuran sanad dan matan haÂÂdis melalui sumber yang banyak dan yang dijadikan fokus kajian adalah HR. Imam at-Turmudzy dapat disimpulkan bahwa hadis dimaksud adalah berkuÂaliÂtas sahih. Dengan demikian, al-Quran sebagai bacaan sempurna bagi umat Islam yang memiliki kaidah tertentu dalam membacanya, mulai dari penyebutan huÂruf-hurufnya, panjang pendeknya, tebal tipisnya serta ketentuan makharijul huÂrufnya perlu dipelajari dan diajarkan secara tekun dan sungguh-sungguh. Belajar al-ÂQuran mencakup upaya mempelajari cara membacanya, terjemah, dan memaÂhaÂmi hukum-hukum, pelajaran-pelajaran, petunjuk-petunjuk yang terkandung di daÂlamnya. Begitu pula, mengajarkan al-Quran mencakup upaya menuntun dan memÂbimbing orang dalam membaca, menerjemah dan memahamkan kandungan ayat-ayat al-Quran. Orang yang melakukannya secara ikhlas dan sungguh-sungÂguh akan mendapatkan keutamaan dari al-Quran berupa ketenangan, ketenteÂraÂmÂan hati dan pikiran serta syafaat di akhirat kelak.